Characteristics of anti-hepatitis C virus antibody-positive patients in a hospital setting in Douala, Cameroon. (April 2016) - Luma, Henry Namme; Eloumou, Servais Albert Fiacre Bagnaka; Malongue, Agnes; Temfack, Elvis; Noah, Dominique Noah; Donfack-Sontsa, Olivier; Ditah, Ivo Che
Highlights: There is an urgent need to put in place programs to increase awareness, diagnosis, and treatment of hepatitis C virus (HCV) infection in Cameroon. Anti-HCV antibody-positive participants were studied in Douala General Hospital Almost 40% were asymptomatic. A history of blood transfusion, surgery, and scarification remain potential risk factors. Clinical examination and baseline blood biochemistry are very useful at initial assessment. Almost half of patients presented with advanced liver fibrosis, METAVIR F3/F4. Genotype 1 was most common. Summary: Introduction: Hepatitis C virus (HCV) infection is a major public health problem, especially in resource-limited settings where many patients are diagnosed at the stage of complications. In Cameroon, where HCV is endemic, little is known about the clinical, biological, and virological profile of HCV-infected patients. Methods: A clinical case note review of all patients positive for antibodies against HCV diagnosed at the gastroenterology outpatient clinic of the Douala General Hospital, Cameroon, from January 2008 to December 2014, was performed. Results: A total of 524 patients were included in the study, 53% of whom were female. The mean age was 56 ± 13 years. A history of blood transfusion and a history of scarification were the most common potential risk factors for HCV exposure, as found in 16% and 13% of the study population, respectively. Current alcohol use was found in 24% of patients. Co-infection with hepatitis B virus and HIV was 3.6% and 3.4%, respectively. Among the patients, 39% had no complaint at diagnosis; only 16% were diagnosed through a routine medical checkup. Clinically, the most common finding was hepatomegaly (26.1% of patients). Transaminases above the upper limit of normal were found in 55.2% of patients, particularly those aged >57 years ( p  = 0.001). Genotypes 1 (43.95%), 2 (25.11%), and 4 (28.25%) were the most common. Liver cirrhosis was present in 11% of patients and hepatocellular carcinoma in 4%, the latter being more common in males ( p  < 0.001) and in those aged >57 years ( p  = 0.03). Conclusions: In the gastroenterology clinic of Douala General Hospital, while almost 40% of patients who were anti-HCV antibody-positive were asymptomatic and diagnosed fortuitously, some already presented complications, including cirrhosis and hepatocellular carcinoma. There is an urgent need to put in place programs to increase awareness and diagnosis of HCV infection and to develop extensive and targeted anti-HCV treatment guidelines to improve the management of these patients in Cameroon.